Integration of Quality Management and Risk Control in Islamic Educational Institutions: Synergy for Effectiveness and Sustainability - Nurisah, Nurisah; Hayati, Siti Rahma; Idrus, Ali Jadid Al; Maimun, Maimun (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
As a primary pillar of civilization, education demands quality implementation. However, the reality on the ground shows the existence of various risks that have the potential to degrade the quality of education. In the context of Islamic Educational Institutions, this presents a double challenge, because Islamic educational institutions are not only concerned with technical-administrative aspects, but also bear moral and spiritual burdens. Some of the problems that arise include limited resources, where many Islamic educational institutions face shortages in human and financial resources that impact the quality of teaching. Therefore, synergy between quality management and risk management is imperative to ensure the continuity of a superior educational process. Departing from this urgency, this study proposes two main problem formulations: how to internalize quality management in the operations of Islamic educational institutions to improve the quality of education, and what efforts can be made to manage and mitigate risks that threaten the integrity of education in these institutions. (1) How are quality management-based risk control strategies? (2) How is quality management implemented in risk control in educational institutions? The findings in this study include two points: First, to create a quality Islamic educational institution, quality management must involve all elements within the institution and be implemented systematically. This process encompasses planning, organizing, and implementation. Second, to create an effective and sustainable Islamic educational institution, the integration of quality management and risk control is crucial. By integrating quality and risk management, the institution can not only ensure operational sustainability but also maintain its Islamic identity.